Chromolaena odorata - the invincible invader - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
The spread of the weed Chromolaena odorata formerly known as Eupatorium odoratum, which was only recently introduced into the continent, is assuming worrying proportions. The plant is taking over as forests in the tropical humid zones of Africa are...